Genotoxic and phytotoxic risk assessment of fresh and treated hydrochar from hydrothermal carbonization compared to biochar from pyrolysis - Busch, Daniela; Stark, Arne; Kammann, Claudia I.; Glaser, Bruno (Ecotoxicology and environmental safety, 2013)
Biochar is discussed as an option for climate change mitigation via C sequestration and may promote sustainable resource efficiency. Large-scale field trials and commercial business with char materials have already started. Therefore char materials have to be assessed for toxic compounds. We tested genotoxic effects of different hydrochars and biochars with the Tradescantia micronucleus test. For this purpose chromosomal aberrations in pollen cells of Tradescantia in the form of micronuclei were evaluated microscopically after defined exposition to extracts from char materials. Hydrochars from hydrothermal carbonization mostly exhibited significantly negative results. Additional germination experiments with hydrochar showed total germination inhibition at additions above five percent v/v in comparison to biochar. However, biological post-treatment of previously toxic hydrochar was successful and toxic effects were eliminated completely. Some post-treated hydrochars even showed growth stimulating effects. Our results clearly demonstrate the necessity of risk assessment with bioindicators. The chosen tests procedures can contribute to biochar and hydrochar characterization for safe application. •We modified the genotoxicity assay with Tradescantia for evaluation of hydrochar and biochar.•Genotoxic as well as phytotoxic effects of some hydrochars were demonstrated in additional germination tests.•The effects can be removed by chemical or biological post treatment.•We revealed a significant increase of biomass in germination tests with composted hydrochars.